Marital Status and Its Effect on Depression in Indonesia: A Case Study of the 2014 Indonesian Family Life Survey - Adrian Kevianta Anggana; Aviliani Aviliani; Patron Natadjaya Ramadhanu Badrudin; Estro Dariatno Sihaloho (Disease Prevention and Public Health Journal, 2022)
Background: Depression is a mental health disorder that makes the sufferer unmotivated and unproductive. This is caused by some factors such as loneliness, perfectionism, and marital status. Riset Kesehatan Dasar (Riskesdas) in 2018 shows that 6.1 percent of the population aged 15 and above in Indonesia experienced depression. Therefore, this study aims to see how marital status affects depression in Indonesia. Method: This study uses logistic regression, marginal effect, and the Rasch model using data from the Indonesian Family Life Surveys (IFLS) in 2014/2015. Result: Analyses showed that married observations have a lower prevalence of depression compared to those who are not married, divorced, or widowed. Conclusion: Therefore, an increase in divorce cases will increase the prevalence of depression in Indonesia. More effort in educating marriage to young couples is needed to reduce the number of divorces in Indonesia.